Therapist Adherence to Two Treatments for Adolescent Suicide Risk: Association to Outcomes and Role of Therapeutic Alliance. Issue 1 (27th April 2021) - Ibrahim, Maliha; Levy, Suzanne; Gallop, Bob; Krauthamer Ewing, Stephanie; Hogue, Aaron; Chou, Jessica; Diamond, Guy
Abstract : In psychotherapy research, adherence refers to the extent to which therapists deliver a treatment as intended. This study examined whether therapist adherence to two different manualized treatments was associated with improved client outcomes and whether the association was moderated by therapeutic alliance. The study sample included 320 video recordings of therapy sessions from 118 cases in a randomized controlled trial (RCT) comparing attachment‐based family therapy (ABFT) with family‐enhanced nondirective supportive therapy (FE‐NST). Recordings were selected from early, middle, and late stages of treatment. The adherence measure consisted of 24 items representing essential therapist interventions from both treatments. Trained raters coded tapes from both therapies. Adolescent self‐report of alliance was measured at session 4. Adherence to ABFT was associated with a significant increase in family cohesion at mid‐treatment but not at posttreatment. Adherence to FE‐NST was significantly associated with an increase in suicide ideation posttreatment. Using therapeutic alliance as a moderator, adherence to ABFT was significantly associated with a reduction in suicide ideation, family conflict, and higher client satisfaction posttreatment. Alliance did not positively affect the association of FE‐NST adherence to outcomes. Findings suggest that adherence to ABFT interventions may be better linked to treatment outcomes when adolescents feel a strong alliance with their therapist. Implications for future research and therapist training are explored. Resumen: En la investigación sobre psicoterapia, la adhesión se refiere al grado en el cual los terapeutas brindan un tratamiento según lo previsto. Este estudio analizó si la adhesión del terapeuta a dos tratamientos estandarizados diferentes estuvo asociada con mejores resultados en los pacientes y si la asociación estuvo moderada por la alianza terapéutica. La muestra del estudio incluyó 320 videograbaciones de sesiones de terapia de 118 casos en un ensayo aleatorizado controlado donde se comparó la terapia familiar basada en el apego (TFBA) con la terapia de apoyo no directiva optimizada por la familia (TAND‐OF). Se eligieron grabaciones de las etapas iniciales, intermedias y finales del tratamiento. El instrumento de medición de la adhesión consistió en 24 ítems que representaban intervenciones esenciales del terapeuta de ambos tratamientos. Un grupo de calificadores capacitados codificaron las grabaciones de ambas terapias. El autoinforme de alianza de los adolescentes se midió en la cuarta sesión. La adhesión a la TFBA estuvo asociada con un aumento considerable de la cohesión familiar en la mitad del tratamiento, pero no después del tratamiento. La adhesión a la TAND‐OF estuvo asociada considerablemente con un aumento de la ideación suicida después del tratamiento. Utilizando la alianza terapéutica como moderadora, la adhesión a la TFBA estuvo asociada considerablemente con una reducción de la ideación suicida, el conflicto familiar y una mayor satisfacción del paciente después del tratamiento. La alianza no afectó positivamente la asociación de la adhesión a la TAND‐OF con los resultados. Los resultados sugieren que la adhesión a las intervenciones de TFBA puede asociarse mejor con los resultados del tratamiento cuando los adolescentes sienten una alianza fuerte con su terapeuta. Se analizan las implicancias para futuras investigaciones y para la capacitación de los terapeutas. 摘要: 在心理治疗研究中, 治疗一致性是指治疗师按照预设方案提供治疗的程度。本研究考察了治疗师自始至终地执行两种不同的遵循手册式的治疗是否与改善病人治疗结果相关, 以及治疗联盟是否调节了这种关联性。研究样本包括来自118例随机对照试验(RCT)的320个治疗过程的视频记录, 试验比较了基于依恋的家庭治疗(ABFT)和家庭赋能强化的非指导性的支持治疗(FE‐NST) 这两种方式。从治疗的早期、中期和晚期选取视频记录。治疗一致性措施由24个项目组成, 代表两种治疗手段中的基本的治疗师干预。训练有素的评价员对两种疗法的视频进行编码。在第4阶段测量了青少年关于联盟的自我报告。忠实执行ABFT与治疗中期的家庭凝聚力显著增加有关联, 但治疗后并没有。遵循FE‐NST的治疗与治疗后自杀意念增加显著相关。以治疗联盟作为调节因子, 坚持ABFT与治疗后自杀意念的减少、家庭冲突减少和更高的病人满意度显著相关。联盟对FE‐NST坚持治疗的一致性结果没有积极影响。研究结果表明, 当青少年感觉与他们的治疗师有很强的联盟时, 坚持ABFT干预可能与治疗结果有更好的联系。本文对未来的研究和治疗师培训的启示都进行了探讨。